(untitled) (Revista Científica Integrada, 2024)
Objective: to evaluate the application of robotic heart surgery and the opportunities with the application of 5G. Method: this is a literature review, conducted in PUBMED/MEDLINE, using the descriptors: “Thoracic Surgery”, “Robotic Surgical Procedures”, “Cardiology” and “Internet” separated by the Boolean operator AND. The selection process consisted of four stages: identification, selection, eligibility, and inclusion comprising 18 articles. Results: it was identified that there was an increase in the use of robotic heart surgery due to less surgical trauma, shorter hospitalization time without complications, functional gain with earlier return to daily activities and secondary aesthetic gain, as well as the perception of greater satisfaction of the patient. With 5G, there is a possibility that the effects of this type of surgery will transcend to a better level of quality and access. Conclusion: robotics has significantly improved the surgical field of cardiology. Advances have changed traditional therapeutic algorithms, making them viable and effective. 5G is an opportunity to progress in robotic techniques, democratize knowledge and access, even if it requires logistics and technical expertise. There is no adequate number of practical studies to assess its applicability.